Combined Nitrogen‐Isotope and Cyclostratigraphy Evidence for Temporal and Spatial Variability in Frasnian–Famennian Environmental Change. (12th May 2022) - Percival, L. M. E.; Marynowski, L.; Baudin, F.; Goderis, S.; De Vleeschouwer, D.; Rakociński, M.; Narkiewicz, K.; Corradini, C.; Da Silva, A.‐C.; Claeys, P.
Abstract: Widespread marine anoxia triggered by the runoff and recycling of nutrients was a key phenomenon associated with the Frasnian–Famennian (FF) mass extinction. However, the relative importance of global‐scale processes versus local influences on site‐specific environmental change remains poorly understood. Here, nitrogen‐isotope (δ 15 N) trends are combined with organic‐biomarker, phosphorus, and Rock‐Eval data in FF sites from the USA (H‐32 core, Iowa), Poland (Kowala Quarry), and Belgium (Sinsin). Up‐to‐date cyclostratigraphic age models for all three sites allow the nature and timing of changes to be precisely compared across the globe. Negative δ 15 N excursions across the FF interval from the H‐32 core and Kowala correlate with geochemical evidence for euxinic, phosphorus‐rich, water columns, and possible cyanobacterial activity, suggestive of increased diazotrophic N fixation, potentially coupled with ammonium assimilation at the latter site. By contrast, previously studied sites from Western Canada and South China document enhanced water‐column denitrification around the onset of the Upper Kellwasser (UKW) Event, re‐emphasizing the geographical heterogeneity in environmental perturbations at that time. Moreover, environmental degradation began >100 kyr earlier in Poland, coeval with a major increase in bioavailable phosphorus supply, than in Iowa, where no such influx is recorded. These regional differences in both the timing and nature of marine perturbations during the FF interval likely resulted from the variable influx of terrigenous nutrients to different marine basins at that time, highlighting the importance of local processes such as terrestrial runoff in driving environmental degradation during times of climate cooling such as the UKW Event. Plain Language Summary: The Frasnian–Famennian mass extinction, ∼372 million years ago, marked one of the most severe biological crises in Earth's history. The extinction has been linked to rapid climate changes and reduced seawater oxygen levels across the global ocean. However, the degree to which environmental stress was globally versus locally controlled remains unclear. This study presents geochemical markers of water‐column oxygenation and nutrient cycling (nitrogen isotopes, phosphorus contents, organic biomarkers) at three localities, the H‐32 core (Iowa, USA), the Kowala Quarry (Poland), and Sinsin (Belgium). The unique feature of these records is the existence of precise age‐depth models, allowing direct comparison of the timing of environmental changes between these sites, and with other key sections from Western Canada and South China. It is shown that whilst the H‐32 core and Kowala indicate possible increases in cyanobacterial nitrogen fixation under phosphorus‐rich, oxygen‐ and nitrate‐depleted conditions, other sites show markedly different nitrogen‐cycle disturbances, such as enhanced water‐column denitrification. Additionally, environmental stress commenced earlier in Kowala than elsewhere, coincident with elevated phosphorus influx to that setting. These regional variations in the timing and nature of environmental perturbations emphasize the importance of local processes such as terrestrial nutrient runoff in causing the Frasnian–Famennian extinction. Key Points: Nitrogen‐isotope records of globally variable environmental change in the Frasnian–Famennian crisis Combination with age models highlights further variability in the onset of those changes Multi‐proxy geochemistry highlights nutrient runoff as trigger of earliest anoxia